The spice industry in Tanzania: General profile, supply chain structure, and food standards compliance issues - Adam Akyoo; Evelyne Lazaro (Danish Institute for International Studies (DIIS), 2007)
The fall in the agricultural sector's contribution to Tanzanian export earnings since the early 1990s has increased attention toward new crops with the potential of supplementing the country's traditional export crops. Particular attention has been focused upon identifying crops enjoying price stability, high demand elasticity and low substitutability. Spices fall into this category. Consequently there have been efforts by public agencies and private exporters, both on the mainland and on Zanzibar, to promote the crop. However, access to high value export markets raises issues of supply chain dynamics and conformity with international standards. This paper focuses upon the recent history of the spice industry in Tanzania with reference to these issues. The main conclusions are that Certified Organic standards are the only international standards complied with, and that a very loosely coordinated chain exists alongside a more coordinated one. Macro- and micro-institutional weaknesses need attention if the full potential of the sub-sector is to be realized.
Keywords: 330; Gewürz; Export; Produktpolitik; Tansania